Translating emotion words in a Japanese healing fiction – Days at the Morisaki Bookshop - Normalis Amzah; Azalia Zaharuddin; Roswati Abdul Rashid (Penerbit Universiti Kebangsaan Malaysia, 2025)
Studies on emotion words indicate that they tend to be culture-specific, as there is an inclination for different cultures to use words that are difficult to translate literally due to their cultural attributes. Although numerous studies have explored emotion words, many of them have not considered emotions as cultural-specific items. Therefore, this study is conducted to explore emotion words from one specific culture and to investigate how these words are translated into the English language. The novel ‘Days at the Morisaki Bookshop’ was chosen because it is considered as one of the ‘healing’ fictions, and thus centres around the emotions of its characters. To explore the emotion words, firstly, the study chose the most significant emotions words in the book by counting the frequency of its appearance in the book. Next, the translation strategies were analysed by comparing both the original Japanese text and its English translation. This analysis of translation strategies was used to deconstruct Japanese emotion words and to discuss how they were translated in ways that fit into the emotional realm of readers from a different culture. The findings show generic emotion are the most frequent emotion words in the source text, followed by positive emotion words, ‘suki’ and ‘aisuru’, which literally mean ‘like’ and ‘love’. The next most frequent are the negative emotion words, ‘shinpai’ and ‘okoru’, which literally mean ‘worry’ and ‘angry’. Japanese often expresses emotions through specific words, while English tends to show emotions through actions or context. Translators may leave out emotion words to match English styles, which prefer clear, natural, and less direct expressions. This approach reflects cultural differences and helps keep the emotional meaning and effect when moving between languages.